The association of problematic eating behaviours with food quality and body mass index at 7 years of age - Costa, S (2018)
Background/objectives: There is scarce evidence of how certain eating behaviours compromise the compliance with dietary guidelines and weight status in school-aged children. This study aims to evaluate the association of children’s problematic eating behaviours with food quality and body mass index at 7 years of age. Subjects/methods: Participants were children aged 7 years old from a population-based cohort study from Porto, Portugal-Generation XXI. Children’s quantity and speed of ingestion, food refusal at the table and food rewards requesting were evaluated by caregiver’s perception. Food consumption was evaluated by a food frequency questionnaire and compared with age-appropriate guidelines. Children’s weight status was assessed by objective measurements and parent’s perceptions. Associations were estimated by logistic regressions (odds ratio (OR), 95% confidence intervals (95% CI)) adjusted for maternal age, education, smoking during pregnancy, birth type, child’s sex, weight-for-gestational age and sports (n = 3801). Results: Children eating small amounts of food, refusing to eat at the table with the rest of the family during meals and asking for food rewards showed a higher consumption of energy-dense foods (OR = 1.51; 95% CI:1.23–1.86; OR = 1.58; 95% CI:1.16–2.16; OR = 1.56; 95% CI:1.14–2.12) and presented higher odds of consuming fruit and vegetables below recommendations (OR = 1.41; 95% CI:1.22–1.64; OR = 1.20; 95% CI:1.00–1.45; OR = 1.28; 95% CI:1.05–1.55). Children displaying these eating behaviours were less likely to be overweight/obese, hence their parents were less likely to show concern with their weight. Including food quality as covariate in the final models with obesity status did not change the associations. Conclusions: Problematic eating behaviours were associated with poorer food quality (more energy-dense foods and low fruit and vegetables), but food quality does not seem to explain the association with obesity status. Parents were less likely to be concerned about their child’s weight if the child ate slowly or poorly, and accordingly the odds of them being overweight or obese were lower.